Answer:
![4x^(5) y^(6) √(7y)](https://img.qammunity.org/2023/formulas/mathematics/college/c196cef70vbetapp189dpl7m9b2mmkesze.png)
Explanation:
1) Separate the radicals
sqrt(112x^10y^13) = sqrt(112)*sqrt(x^10)*sqrt(y^13)
2) For sqrt(112), rewrite it as the product of a perfect square and some other number.
sqrt(112) = sqrt(16) * sqrt(7)
= 4*sqrt(7)
3) For sqrt(x^10), rewrite it in terms of it being raised to a fraction
![\sqrt[n]{x} = x^{(1)/(n) }](https://img.qammunity.org/2023/formulas/mathematics/college/4o0rsucdw46495j9i1oia3kjhsseyxgkl5.png)
n = 2, so x^(10/2), and when simplified you have x^5
4) For sqrt(y^13), do the same thing.
y^(13/2) = sqrt(y)*(y^6)
5)Combine everything
4x^5y^6sqrt(7y)